Effects of 3% Mobe (Artocarpus lakoocha) leaf extract gel on the post-extraction socket: In-vivo study - Hanafiah, Olivia Avriyanti; Hanafiah, Diana Sofiah; Dohude, Gostry Aldica; Satria, Denny; Putri, Maharani Syahnia; Harahap, Nurul Izzatunna Jhirah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Mobe (Artocarpus lakoocha) is recognized for its potential in accelerating wound healing, attributed to its secondary metabolites. However, its impact on hard tissue healing on post- extraction tooth sockets has been underexplored. Purpose: This study aims to analyze the effects of 3% Mobe leaf extract gel on the number of fibroblasts, osteoblasts, osteocytes and post-extraction sockets in Wistar rats. Methods: Thirty-two male Wistar rats had their left mandibular incisors extracted and were divided into eight groups. Mobe leaf extract gel was applied to Group I-IV and Aloclair® gel was applied to Group V-VIII for 14 days, twice a day. Residual socket volume (RSV) and fibroblast counts were measured on days 3, 7, and 14, while osteoblast and osteocyte counts were assessed on days 7, 14, and 28 post extraction. The RSV data were analyzed using repeated measures analysis of variance (ANOVA) and post-hoc least significant difference (LSD) test, while fibroblasts, osteoblasts, and osteocytes counts were analyzed with one-way ANOVA and post-hoc LSD tests. Results: RSV decreased significantly in both groups on day 14 (p=0.001 and p=0.002); however, the RSV was lower on the Mobe group. The fibroblast counts were higher in the Mobe group (p=0.001), and there was a significant difference in the mean number of osteoblasts and osteocytes in the Mobe group (p= 0.043 and p=0.008). Conclusion: The study concludes that 3% Mobe leaf gel extract is better than Aloclair® in accelerating socket healing mainly due to increased proliferation of fibroblasts, osteoblasts, and osteocytes.